The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-07353-7
|View full text |Cite
|
Sign up to set email alerts
|

Corneal nerve loss in patients with TIA and acute ischemic stroke in relation to circulating markers of inflammation and vascular integrity

Abstract: Vascular and inflammatory mechanisms are implicated in the development of cerebrovascular disease and corneal nerve loss occurs in patients with transient ischemic attack (TIA) and acute ischemic stroke (AIS). We have assessed whether serum markers of inflammation and vascular integrity are associated with the severity of corneal nerve loss in patients with TIA and AIS. Corneal confocal microscopy (CCM) was performed to quantify corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD) and cornea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Tear IL-6 level was shown to be inversely correlated with corneal nerve density in patients with bacterial keratitis [ 50 ]. The circulating level of IL-6 was significantly associated with corneal nerve fiber loss in patients with transient ischemic attack and acute ischemic stroke [ 51 ]. Moreover, an elegant study by Chucair-Elliott et al [ 52 ] reported that IL-6 was increased in the murine cornea after herpes simplex virus (HSV) infection, and that IL-6 suppression by either neutralizing Ab or dexamethasone reduced corneal nerve regression, thereby preserving sensation in HSV keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Tear IL-6 level was shown to be inversely correlated with corneal nerve density in patients with bacterial keratitis [ 50 ]. The circulating level of IL-6 was significantly associated with corneal nerve fiber loss in patients with transient ischemic attack and acute ischemic stroke [ 51 ]. Moreover, an elegant study by Chucair-Elliott et al [ 52 ] reported that IL-6 was increased in the murine cornea after herpes simplex virus (HSV) infection, and that IL-6 suppression by either neutralizing Ab or dexamethasone reduced corneal nerve regression, thereby preserving sensation in HSV keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased permeability of the BBB can be attributed to MMP related proteolytic degradation of the basal lamina and TJs [83] . MMP-9 is activated in hypoxic conditions [84] , found to be elevated in VCD [85] and stroke patients [86] as well as associated with cognitive decline and worsening neurological outcomes. Though elevated blood MMP-2 levels have also been reported in VCD subjects with multiple infarcts and stroke [87] , results for MMP-3 levels in cerebrovascular disorders were conflicting (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal nerve loss occurs in patients with mild cognitive impairment and dementia, is related to cognitive dysfunction and functional independence and predicts conversion to dementia in subjects with mild cognitive impairment [5]. Corneal nerve loss also occurs in patients with transient ischaemic attack and stroke and is associated with cardiovascular risk factors and pial collateral status [6]. Similar to diabetic neuropathy, CCM has shown superior diagnostic performance for diagnosing multiple sclerosis, Parkinson's disease and dementia compared to gold standard testing.…”
mentioning
confidence: 99%